INOVASI PENDIDIKAN ISLAM MASA PANDEMI COVID 19 DI MA AL URWATUL WUTSQO JOMBANG - Ali Mustofa (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2021)
Pandemic of Coronavirus Disease (Covid-19) in Indonesia has changed all education models, including in Jombang. Many problems changes for school education. Such as teachers are facing hard challenges. Educators are required to be creative in delivering material through online learning media. It also needs to be invincible with the level of educational needs. MA Al Urwatul Wutsqo Jombang makes effort to deliver Islamic education even in pandemic conditions. This is done through online and offline. The online or distance learning has been carried out in several ways, namely the delivery of materials and assignments through the e-learning program, email, What Sapp and using virtual face through zoom meeting application. Meanwhile the offline is done by taking an assignment in the morning at school and collected on the following day, then next is limited meeting that is reducing face-to-face hours, and designing classes based on the health protocols.